Nursing Leadership and Liability: An Analysis of a Nursing Malpractice Case - Cooper, Patricia J. (Nurse leader, 2016)
Nursing care delivery is a critical factor in patient care outcomes. Nurses must be knowledgeable, skillful, and agile, and must apply these characteristics consistently, without pause, every second of their practice. The National Practitioner Data Bank (NPDB) collects and releases information related to professional competence and conduct of a multitude of health care practitioners, including all levels of nursing.1 According to the NPDB, in 2012, there were 22,741 adverse actions related to nurses’ practice. This figure is nearly double the number of actions related to nurses reported in 2003 (12,289). Similarly, medical malpractice reports demonstrated an increase from 483 in 2003 to 711 in 2012.1